2020
DOI: 10.1111/cas.14286
|View full text |Cite
|
Sign up to set email alerts
|

Abemaciclib, a CDK4/6 inhibitor, exerts preclinical activity against aggressive germinal center‐derived B‐cell lymphomas

Abstract: The revised WHO classification newly defined the entities "High-grade B-cell lymphoma with MYC and BCL2, and/or BCL6 rearrangements (HGBL-DH/TH)" and "HGBL, NOS." Standard immunochemotherapy for diffuse large B-cell lymphoma (DLBCL), R-CHOP, is insufficient for HGBL patients, and there are currently no optimized therapeutic regimens for HGBL. We previously reported that CCND3, which encodes cyclin D3, harbored high mutation rates in Burkitt lymphoma (BL), HGBL and a subset of DLBCL. Furthermore, the knockdown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Palbociclib was shown to effectively arrest cell cycle progression and tumor growth in several cancers, including hepatocellular carcinoma [25,26], glioblastoma [15,16,27], synovial sarcoma [28], medulloblastoma [19,29], AT/RTs [18], and gastric cancers [30]. Abemaciclib was also found to effectively induce cell cycle arrest and tumor growth inhibition in several cancers, including non-small cell lung cancer [22], glioblastoma [17], Ewing's sarcoma [31], multiple myeloma [32], and aggressive germinal center-derived B-cell lymphomas [33]. In this study, we demonstrated that abemaciclib treatment resulted in decreased expression of genes related to the cell cycle and DNA repair through inhibiting RB phosphorylation and total RB protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…Palbociclib was shown to effectively arrest cell cycle progression and tumor growth in several cancers, including hepatocellular carcinoma [25,26], glioblastoma [15,16,27], synovial sarcoma [28], medulloblastoma [19,29], AT/RTs [18], and gastric cancers [30]. Abemaciclib was also found to effectively induce cell cycle arrest and tumor growth inhibition in several cancers, including non-small cell lung cancer [22], glioblastoma [17], Ewing's sarcoma [31], multiple myeloma [32], and aggressive germinal center-derived B-cell lymphomas [33]. In this study, we demonstrated that abemaciclib treatment resulted in decreased expression of genes related to the cell cycle and DNA repair through inhibiting RB phosphorylation and total RB protein levels.…”
Section: Discussionmentioning
confidence: 99%
“…While both agents induced autophagy with different intensities, abemaciclib additionally increased early apoptotic cells, while dinaciclib predominantly evoked necrosis. CDKi-mediated apoptosis has been described in various tumor models 19 23 . By contrast, autophagy was only recently described for abemaciclib 24 and just one publication described the cytoprotective role of autophagy under dinaciclib therapy in NSCLC 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Cyclin-dependent kinase 4 (CDK4), a crucial player in cell cycle progression, is associated with DLBCL. The CDK4 inhibitor abemaciclib strongly suppresses cell proliferation and induces apoptosis in DLBCL [ 57 ]. The present results point to a strong positive correlation between CDK4 and the TFs KZF1 and NCAPG.…”
Section: Discussionmentioning
confidence: 99%